2015
DOI: 10.1088/0957-4484/26/26/265201
|View full text |Cite
|
Sign up to set email alerts
|

Rapid synthesis of ultra-long silver nanowires for tailor-made transparent conductive electrodes: proof of concept in organic solar cells

Abstract: Rapid synthesis of ultralong silver nanowires (AgNWs) has been obtained using a one-pot polyol-mediated synthetic procedure. The AgNWs have been prepared from the base materials in less than one hour with nanowire lengths reaching 195 μm, which represents the quickest synthesis and one of the highest reported aspect ratios to date. These results have been achieved through a joint analysis of all reaction parameters, which represents a clear progress beyond the state of the art. Dispersions of the AgNWs have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 43 publications
(58 reference statements)
2
79
0
Order By: Relevance
“…For all subsequent syntheses, the process time was kept at 30 min to ensure a completed wire growth. This time compares well or is even shorter than studies that report a duration of 30 min [28], 60 min [6,29,30], and 120 min [31] for their standard process.…”
Section: Solution-based Synthesis Of Silver Nanowiressupporting
confidence: 64%
See 3 more Smart Citations
“…For all subsequent syntheses, the process time was kept at 30 min to ensure a completed wire growth. This time compares well or is even shorter than studies that report a duration of 30 min [28], 60 min [6,29,30], and 120 min [31] for their standard process.…”
Section: Solution-based Synthesis Of Silver Nanowiressupporting
confidence: 64%
“…Finally, for the synthesis section of this work, the effect of the addition of the halide KCl was studied. So far, a few studies have presented the use of halides such as KBr for the synthesis of AgNWs and reported a reduction in diameter [28,31,42,46,47]. For adding different concentrations of KCl (3-15 wt.%, see supporting information Figure S-6), we have also observed a modulation in diameter, which lies in the range of 78-114 nm.…”
Section: Solution-based Synthesis Of Silver Nanowiressupporting
confidence: 52%
See 2 more Smart Citations
“…Silver nanowires (AgNWs) have been extensively studied during past years. They exhibit high conductivity(~105 Scm´1) without any detrimental effects to their high transparency (>90%) [11]. Regarding the synthesis of silver nanowires several methods have been reported including hard-template [12,13] and soft template synthesis [14].…”
Section: Introductionmentioning
confidence: 99%